White common bean extract remodels the gut microbiota and ameliorates type 2 diabetes and its complications: A randomized double-blinded placebo-controlled trial - Feng, Yuwei; Zhu, Jie; Wang, Qinyue; Cao, Hong; He, Fang; Guan, Yin; Li, Dan; Yan, Jiai; Yang, Ju; Xia, Yanping; Dong, Meihua; Hu, Feng; et al. (Frontiers in Endocrinology, 2022)
Objective Excessive carbohydrate intake is a high risk factor for increased morbidity of type 2 diabetes (T2D). A novel regimen for the dietary care of diabetes that consists of a highly active α-amylase inhibitor derived from white common bean extract (WCBE) and sufficient carbohydrates intake was applied to attenuate T2D and its complications. Furthermore, the role of gut microbiota in this remission was also investigated. Methods We conducted a 4-month randomized double-blinded placebo-controlled trial. During the intense intervention period, ninety subjects were randomly assigned to the control group (Group C) and WCBE group (Group W). Subjects in Group C were supplemented with 1.5 g of maltodextrin as a placebo. Subjects in Group W took 1.5 g of WCBE half an hour before a meal. Fifty-five participants continued the maintenance intervention receiving the previous dietary intervention whereas less frequent follow-up. The variation in biochemical, vasculopathy and neuropathy indicators and the structure of the fecal microbiota during the intervention was analyzed. Result Glucose metabolism and diabetic complications showed superior remission in Group W with a 0.721±0.742% decline of glycosylated hemoglobin after 4 months. The proportion of patients with TCSS≥6 was significantly lower in Group W than in Group C at the end of 4 months. Both the left and right sural sensory nerve conduction velocity (SNCV-left sural and SNCV-right sural) slightly decreased in Group C and slightly increased in Group W. Additionally, the abundances of Bifidobacterium, Faecalibacterium and Anaerostipes were higher in Group W, and the abundances of Weissella, Klebsiella, Cronobacter and Enterobacteriaceae_unclassified were lower than those in Group C at month 2. At the end of month 4, Bifidobacterium remained more abundant in Group W. Conclusion To our knowledge, this is the first report of improvement to diabetes complications by using a dietary supplement in such a short-term period. The enrichment of SCFA-producing bacteria might be responsible for the attenuation of T2D and its complications.